1992
DOI: 10.1002/ar.1092320106
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrically banded collagen fibrils: Observations on a new cross striation pattern in vivo

Abstract: Collagen fibrils with a symmetric banding pattern, an as yet overlooked component of the extracellular matrix, were found in the reticular layer of the basement membrane of human sebaceous glands. In longitudinal sections this newly described banding pattern is D-periodic (D = 67 nm) resembling the period length of native type collagen fibrils. In cross sections the symmetrically banded fibrils are irregularly outlined. The period length and the symmetric banding pattern led to the assumption that collagen mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…63,64 In that respect the current study offers an interesting model for the formation of some structurally heterogeneous polymorphic forms that can be found in nature. 10,11…”
Section: Transition and Coexistence Of Different Polymorphic Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…63,64 In that respect the current study offers an interesting model for the formation of some structurally heterogeneous polymorphic forms that can be found in nature. 10,11…”
Section: Transition and Coexistence Of Different Polymorphic Formsmentioning
confidence: 99%
“…7 The property of the collagen systems to exhibit varying structural and hierarchical characteristics, else known as collagen polymorphism, has been observed both in vitro 8,9 and in vivo. 10,11 It was shown that the collagen polymorphism is significantly influenced by factors like presence of GAGs, 12,13 other forms of collagen, 14,15 presence/absence of telopeptide regions, 16,17 methods of purification, 18 temperature, 19 pH and salinity of the solutions. 7,20 The numerous reports account for the identification of novel banding patterns, growth mechanisms, and morphological properties of these systems deviating to different extents from the classical collagen type I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that on the scale with which cells interact with their substrate, micropatterning techniques often generate physical structures that may themselves serve to guide focal adhesion (FA) formation. Investigations into the molecular process by which cells adhere to surface motifs demonstrate that cells are sensitive to topographical cues on the nanometer scale; collagen I, II, III, and V fibrils in vivo all present a banding pattern known as the D-period with a regular interval of 67nm [57] . Removal of this D-period in collagen I has been shown to completely erase the ability of aligned fibrils on a 2D substrate to produce cultures of aligned fibroblasts in vitro suggesting a key role played by this pattern in guiding cell alignment [58] .…”
Section: From Constructs To Circuitsmentioning
confidence: 99%
“…26 Although the correct 67 nm D-pattern as seen in microscopy studies appears to be the least discussed feature of collagen I fibrils, the literature still abounds with reports about their property to exhibit varying structural and hierarchical characteristics which are different from the classical collagen I, also known as collagen polymorphism, as observed both in vitro 27,28 and in vivo. 29,30 Amongst the major factors shown to affect it are the presence of GAGs/PGs [31][32][33] and other forms of collagen, 34,35 intactness of telopeptides, 36,37 purification protocols, 38 concentration, 39,40 temperature, 41 pH, and salinity of the solutions. 42,43 The numerous reports also account for the identification of novel banding patterns, growth mechanisms, and morphological properties of these systems deviating to a different extent from the classical collagen type I.…”
Section: Classical Collagen I Self-assembly and Structural Hierarchiesmentioning
confidence: 99%